A Comparative Study of Chronic Subdural Hematoma in Patients With and Without Head Trauma: A Retrospective Cross Sectional Study - Ou, Yunwei; Yu, Xiaofan; Liu, Xiaojuan; Jing, Qian; Liu, Baiyun; Liu, Weiming (Frontiers in Neurology, 2020)
Background: Clinical features in chronic subdural hematomas (CSDH) patients with and without history of head trauma are not clear. Here, we seek to investigate difference of clinical characteristics in CSDH patients with and without head trauma. Methods: Retrospectively collected clinical characteristics of CSDH patients, who were performed exhaustive drainage strategy in burr-hole craniostomy from August 2011 to May 2019. Divided patients into trauma and no trauma groups. Chi-square test or t-test was used to analyze differences of clinical characteristics between two groups. Multiple linear regression analysis was performed to analyze relationships between clinical characteristics and reduction of hematoma cavity and length of hospital stay in CSDH patients with trauma. Results: 1,307 CSDH patients were collected. 805 patients occurred history of head trauma, 502 patients without it. Mean age of patients with trauma was 64.0 ± 16.1 years, while 61.5 ± 17.9 years in patients without trauma (p=0.010). More patients occurred hypertension in without trauma group than trauma group (40.2% vs 32.9%, p=0.007). Dizziness occurred in 29.2% patients with trauma, 23.1% in patients without trauma (p=0.016). Reduction of hematoma cavity after surgery in patients without trauma was less than ones with trauma (p=0.002). Length of hospital stay in patients with trauma was 7.9 ± 4.5 days, which was longer than patients without trauma (7.3 ± 3.7 days, p=0.016). No significantly different densities of hematoma on CT, complications, mortality, recurrence rate and outcome were found between two groups. Conclusion: Pathogenesis and some clinical characteristics occur differences in CSDH patients with and without trauma, but if we choose an optimal treatment method, such as our exhaustive drainage, and we can achieve the same effect.